2022
DOI: 10.1007/s11111-022-00410-3
|View full text |Cite
|
Sign up to set email alerts
|

Floods and maternal healthcare utilisation in Bangladesh

Abstract: Floods are a common natural hazard in Bangladesh, and climate change is expected to further increase flooding frequency, magnitude and extent. Pregnant women in flood contexts could face challenges in utilisation of maternal healthcare. The aim of this paper is to analyse associations between flood exposure and the use of maternal healthcare (antenatal care visits, birth assisted by skilled birth attendants, and giving birth in a health facility) in Bangladesh for pregnancies/births between 2004 and 2018. Bang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“… 29 Contrary to these results, in a study utilising Department of Health Services data in Bangladesh, Orderud et al (2022) initially determined that there was a negative correlation between flooding and MHS usage. 32 However, after controlling for several variables including flood duration, mother’s age at birth, education and occupation, the researchers found no substantial effect, which they theorised was due to disaster mitigation efforts in communities that frequently flood. 32 Furthermore, Haque et al 31 found that women who had been displaced because of floods had 0.18 decreased odds of having delivered their most recent child with medical providers in comparison to women who had not been displaced.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“… 29 Contrary to these results, in a study utilising Department of Health Services data in Bangladesh, Orderud et al (2022) initially determined that there was a negative correlation between flooding and MHS usage. 32 However, after controlling for several variables including flood duration, mother’s age at birth, education and occupation, the researchers found no substantial effect, which they theorised was due to disaster mitigation efforts in communities that frequently flood. 32 Furthermore, Haque et al 31 found that women who had been displaced because of floods had 0.18 decreased odds of having delivered their most recent child with medical providers in comparison to women who had not been displaced.…”
Section: Resultsmentioning
confidence: 97%
“… 32 However, after controlling for several variables including flood duration, mother’s age at birth, education and occupation, the researchers found no substantial effect, which they theorised was due to disaster mitigation efforts in communities that frequently flood. 32 Furthermore, Haque et al 31 found that women who had been displaced because of floods had 0.18 decreased odds of having delivered their most recent child with medical providers in comparison to women who had not been displaced. 31 Only 16.2% of displaced mothers had delivered their most recent child in a health centre, in comparison to 59.8% of non-displaced mothers in the region.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Movement restriction imposed by many government during the COVID-19 pandemic further worsen the issues of accessibility to healthcare. Poor accessibility to health services can lead to increased risk of health effects such as mental health problems, violence, maternal deaths, lower childhood vaccination coverage, and delay in health seeking in emergency situation (13,16,18,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers’ age and education level were the leading factors of maternal healthcare use in these areas. A very recent study measured whether maternal healthcare utilization, both ANC and institutional delivery were affected by the natural disaster, floods [ 62 ]. Though this study found in bivariate analysis that floods have an impact on maternal healthcare usage, the multivariate analysis reveals the opposite conclusion.…”
Section: Literature Reviewmentioning
confidence: 99%